Implementasi Kebijakan Countercyclical Covid-19 Dalam Mitigasi Risiko Pembiayaan Bermasalah - Eva Puji Astuti; Dunyati Ilmiah (LPPM ISNJ Bengkalis, 2022)
This study aims to show the implementation of the countercyclical policy of the Financial Services Authority regulation number 11/POJK.03/2020 and the impact of this policy on the risk of non-performing financing, especially at Bank Syariah Indonesia Godean 3 sub-branch office. This study is qualitative research, with data collection tools in the form of interviews and documentation. Data analysis uses the concept of Miles and Huberman: data reduction, data presentation, and conclusions and verification. The results of this study indicate that the countercyclical policy at Bank Syariah Indonesia Godean 3 sub-branches for all financing segments affected by the covid-19 pandemic, namely financing restructuring in the form of reconditioning and financing quality, has returned to normal. The policy is carried out for one year with a financing assessment based on paying instalments accurately. The impact of the Financial Services Authority regulation number 11/POJK.03/2020 for Islamic banks is a decrease in the non-performing financing portfolio; in addition, the provision for allowance for possible losses on productive assets is also reduced. This research contributes to science, especially countercyclical policies, in overcoming economic problems. Then it can be used by Islamic financial institutions as a reference in dealing with non-natural disasters such as the covid-19 pandemic.